TIRADS Score and Strain Ratio in Elastography to Predict Malignant Thyroid Nodule and Correlation with Histopathology (Bangladesh Journal of Nuclear Medicine, 2026)
Thyroid nodules are a common clinical finding, and accurate differentiation between benign and malignant nodules is essential for appropriate clinical management. This study aimed to evaluate the diagnostic value of the Thyroid Imaging Reporting and Data System (TIRADS) and elastography strain ratio in predicting malignant thyroid nodules and to correlate the findings with histopathology. This study was conducted from 2023 to 2024 and included 30 patients with thyroid nodules referred for ultrasound TIRADS assessment and elastography. Nodules were categorized according to the TIRADS classification system (TIRADS 1–5), and real-time strain ratio (SR) was measured using elastography to assess tissue stiffness. The final diagnosis was confirmed by histopathology following near-total thyroidectomy. The mean age of the patients was 34.1 ± 9.54 years (range 18–55 years), with 80% females. TIRADS demonstrated a sensitivity of 33.33%, a specificity of 93.33%, and an overall accuracy of 63.33%. Elastography strain ratio showed higher diagnostic performance with a sensitivity of 80.00%, a specificity of 93.33%, and an accuracy of 86.67%. Elastography strain ratio appears to be a more reliable method than TIRADS alone for detecting malignant thyroid nodules and may improve diagnostic accuracy in clinical practice.Bangladesh J. Nuclear Med. 28(2): 309-313, July 2025